An attempt to manufacture Cheddar cheese containing only one type of organism : thesis for the degree of M. Agr. Sc. (in Dairy Science) at the University of New Zealand, by Ascend - Neil, William C.; Ascend (Massey University, 1931)
There have been many investigations on the effect of various bacteria on the ripening of hard rennet varieties of cheese. Hucker (1922) in a review of the bacteriological aspects of cheese ripening summaries the position as follows: "As it stands to-day the investigations have closely demonstrated that the breaking down of the insoluble casein compounds is due to enzymes, either natural or bacterial; while characteristic flavors are produced by the action of certain groups of bacteria. (Bacterium casei or coccus group), which depend on the products of B. lactis acidi present in large numbers during the manufature and early ripening stages." The effect of lactic acid bacteria upon the flavour of Cheddar cheese has been studied by Hastings, Evans and Hart (1912), Evans, Hastings and Hart (1914), Evans (1918). Leitch (1923) and Hucker and Marquardt (1926). [From Introduction]
"Ascend" is the nom de plume of William C. Neil
Keywords: Cheddar cheese; Cheese; New Zealand